Financial Risk Aversion and Household Asset Diversification - Nataliya Barasinska; Dorothea Schäfer; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper explores the relationship between self-declared risk aversion of private investors and their willingness to hold diversified portfolios of financial assets. The analysis is based on household survey data from the German Socioeconomic Panel (SOEP) that provides a reliable measure of individual attitude towards financial risk. Our empirical findings suggest that more risk averse investors tend to hold incomplete portfolios that consist mainly of a few safe assets. We also find that for private households the propensity to diversify is highly dependent on whether liquidity and safety needs are satisfied.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: D14; G11; 330; household finances; asset portfolio; diversification; risk aversion